PENGARUH MEDIA PEMBELAJARAN DAN TIPE KEPRIBADIAN TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SD - Safrina Harahap; Zurriyana Nainggolan; Yusmiarn Yusmiarn (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2026)
. This research is motivated by the low achievement of mathematics learning of elementary school students caused by the use of learning media that is less varied and has not paid attention to individual characteristics of students, especially personality types. This study aims to analyze the influence of learning media and personality type on students' mathematics learning achievement. The method used was a quasi-experiment with a 2×2 factorial design, involving 41 third grade students of SD Muhammadiyah 1 Padangsidimpuan. The research variables included learning media (interactive multimedia and magnetic boards) and personality types (introverts and extroverts). Data were collected through learning outcome tests and personality observations, then analyzed using a two-track ANOVA and Tukey's follow-up test. The results showed that there was a significant difference between the use of interactive multimedia and magnetic boards on mathematics learning achievement, where interactive multimedia provided higher results. In addition, there is a significant interaction between learning media and personality type. Interactive multimedia is more effective for introverted students, while magnetic boards are more effective for extroverted students. Thus, the selection of learning media that is suitable for the personality type of students plays an important role in increasing the effectiveness of learning and mathematics learning achievement.